2017
DOI: 10.3389/fpubh.2017.00235
|View full text |Cite
|
Sign up to set email alerts
|

Racial Discrimination in Health Care Is Associated with Worse Glycemic Control among Black Men but Not Black Women with Type 2 Diabetes

Abstract: BackgroundA growing body of research suggests that racial discrimination may affect the health of Black men and Black women differently.AimsThis study examined Black patients with diabetes mellitus (DM) in order to test gender differences in (1) levels of perceived racial discrimination in health care and (2) how perceived discrimination relates to glycemic control.MethodsA total of 163 Black patients with type 2 DM (78 women and 85 men) provided data on demographics (age and gender), socioeconomic status, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 92 publications
6
30
0
Order By: Relevance
“…Assari and Caldwell (2018c) also used a national sample of Black youth and found that discrimination has a stronger effect on Major Depressive Disorder (MDD) of Black boys with higher levels of SES compared to low levels of SES. This finding is supported by other research that has shown that discrimination is more consequential for Black males than Black females (Assari et al., ). The Black men most vulnerable to MDD as a result of discrimination also hold high hegemonic masculinity beliefs (Caldwell, Antonakos, Tsuchiya, Assari, & De Loney, ).…”
Section: Discriminationsupporting
confidence: 86%
“…Assari and Caldwell (2018c) also used a national sample of Black youth and found that discrimination has a stronger effect on Major Depressive Disorder (MDD) of Black boys with higher levels of SES compared to low levels of SES. This finding is supported by other research that has shown that discrimination is more consequential for Black males than Black females (Assari et al., ). The Black men most vulnerable to MDD as a result of discrimination also hold high hegemonic masculinity beliefs (Caldwell, Antonakos, Tsuchiya, Assari, & De Loney, ).…”
Section: Discriminationsupporting
confidence: 86%
“…Racial discrimination, like other forms of systematic oppression, can influence diabetes prevention and care through three main pathways, reflecting interactions with other SDOH, causing (a) lower levels of subpopulation-level SES (owing to lower-quality education and lower-paying jobs), (b) residential segregation (owing to lower income and wealth accumulation, higher rates of unemployment), and (c) psychological distress (due, in part, to fewer quality health care and community services) (139,143). Disparities across communities are often due to structural determinants of racism and discrimination as evidenced by residential segregation, lack of financial services in neighborhoods, or criminal justice policies (10,110,139,143). The For the Sake of All project described the impact of various policies (including financial and housing) and their link to discriminatory practices and negative health and diabetes outcomes of the black population in St. Louis (110).…”
Section: Sociopolitical Contextmentioning
confidence: 99%
“…Racial identity may also alter the effects of discrimination on mental health [ 32 ]. A number [ 27 , 33 , 34 ] but not all [ 10 ] studies have also shown that discrimination may have stronger effects for males than females, particularly in the presence of high masculine ideologies [ 35 ]. An interaction between ethnicity and gender has also been shown to alter these effects [ 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%